1998
DOI: 10.1111/j.1469-7793.1998.565bn.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrogen peroxide and dithiothreitol on contractile function of single skeletal muscle fibres from the mouse

Abstract: We used intact single fibres from a mouse foot muscle to study the role of oxidation‐reduction in the modulation of contractile function. The oxidant hydrogen peroxide (H2O2, 100‐300 μM) for brief periods did not change myoplasmic Ca2+ concentrations ([Ca2+]i) during submaximal tetani. However, force increased by 27 % during the same contractions. The effects of H2O2 were time dependent. Prolonged exposures resulted in increased resting and tetanic [Ca2+]i, while force was significantly diminished. The force d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
405
3
24

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 376 publications
(472 citation statements)
references
References 38 publications
34
405
3
24
Order By: Relevance
“…Several studies have shown that these reactive species contribute to skeletal muscle dysfunction through different mechanisms. Brotto and Nosek [42] demonstrated a decrease in calcium release from the sarcoplasmic reticulum, and Andrade et al [43] demonstrated reduced sensitivity to calcium in muscles exposed to hydrogen peroxide. In addition, moderate oxidative stress has been reported to induce protein oxidation, with a consequent increase in intracellular proteolysis [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that these reactive species contribute to skeletal muscle dysfunction through different mechanisms. Brotto and Nosek [42] demonstrated a decrease in calcium release from the sarcoplasmic reticulum, and Andrade et al [43] demonstrated reduced sensitivity to calcium in muscles exposed to hydrogen peroxide. In addition, moderate oxidative stress has been reported to induce protein oxidation, with a consequent increase in intracellular proteolysis [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of a particular target is defined by the intrinsic sensitivity of the molecule to oxidation–reduction and the local redox state,103 and evidence has shown that RONS produced by skeletal muscle can alter myofilament structure and function 187. Several myofilament proteins including actin, α‐actinin,151, 187 troponin C188 and myosin heavy chains189, 190, 191 are susceptible to RONS‐induced oxidative modifications, thus affecting Ca 2+ dynamics and Ca 2+ sensitivity192 and, inevitably, cross‐bridge kinetics,188 which may result in contractile dysfunction.…”
Section: Non‐enzymatic Key Antioxidants That Contribute To the Maintementioning
confidence: 99%
“…Of many intracellular ROS production mechanisms, the mitochondrion is the most prominent ROS generator wherein constitutive ROS production arises from leakage of a small percent of electrons from the electron transfer chain (ETC) [7,8]. In skeletal muscle, which requires high energy supply and contains abundant mitochondria, adequate amount of ROS modulates muscle contractility and glucose metabolism [9,10], while excessive ROS is responsible for muscle fatigue and insulin resistance [1,11,12].…”
Section: Introductionmentioning
confidence: 99%